2018
DOI: 10.1136/sextrans-2017-053409
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral therapy suppresses rectal HIV-RNA shedding despite inflammation in MSM with rectalC. trachomatisandN. gonorrhoeaeinfections—a cross-sectional, single-center study

Abstract: UTN: U1111-1150-4804. German Clinical Trials Register (DRKS): DRKS00005468.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…5,6 Genital inflammation increases both HIV transmission and acquisition, 7 including clinically diagnosed STI and sub-clinical inflammation. 5,8 Specifically, genital 9,10 and rectal 11 inflammation increase HIV transmission, with the role of STI in HIV transmission diminished by antiretroviral therapy (ART) and HIV suppression. 12 While ART reduces the effects of co-occurring STI on HIV transmission, HIV transmission remains high when ART adherence is incomplete, viral suppression is not sustained, and genital inflammation is present.…”
mentioning
confidence: 99%
“…5,6 Genital inflammation increases both HIV transmission and acquisition, 7 including clinically diagnosed STI and sub-clinical inflammation. 5,8 Specifically, genital 9,10 and rectal 11 inflammation increase HIV transmission, with the role of STI in HIV transmission diminished by antiretroviral therapy (ART) and HIV suppression. 12 While ART reduces the effects of co-occurring STI on HIV transmission, HIV transmission remains high when ART adherence is incomplete, viral suppression is not sustained, and genital inflammation is present.…”
mentioning
confidence: 99%
“…Some limitations identified in this study included the absence of HIV RNA data from HIV-positive participants who did not accept immediate ART and did not have samples collected at 12 and 24 months after baseline. We found that 62% to 65% of MSM in our study had detectable anogenital HIV RNA at baseline which was in the range of 57% to 100% previously reported among men not on ART [26][27][28][29]. However, differences in anogenital sampling and HIV RNA measurement techniques which could affect the detection rate of HIV RNA in these compartments imply that direct comparisons of data between studies may not be simply made [27,28].…”
Section: Discussionmentioning
confidence: 60%
“…STI screening was not conducted in all participants but only in those symptomatic and that may partially explain the relatively low STI prevalence we identified compared with other similar populations [19] and this may also limit the generalizability of the findings. However, recent data suggest that rectal bacterial STIs are not associated with HIV shedding in patients effectively suppressed on ART [20]. Furthermore, in the PIVOT trial, the initial rate of viral rebound on PI-mono was high (32%).…”
Section: Discussionmentioning
confidence: 99%